Effect of Areca Nut on Oral Health: A Review - M Shirzaiy; F Neshat (Islamic Azad University, 2020)
Background and Aim: Oral health can be influenced by habitual areca nut chewing. The consumption of products containing areca nut, such as paan, gutkha, supari, etc., is common in Asian countries, such as India, Bangladesh, and Pakistan. In Iran, areca nut product consumption is common in the southeast of Iran, especially in Chabahar, Iranshahr, and Nikshahr cities, which are in proximity to the Pakistan border. These products are easily accessible in these areas and are widely used due to a lack of awareness about their disadvantages. Areca nut contains tannins and alkaloids, such as arecaidine, guvacine, arecoline, and guvacoline. Arecaidine can stimulate the synthesis of collagen by stimulation and proliferation of fibroblasts. This review article aims to evaluate the effects of areca nut on oral health. Materials and Methods: Research was performed in the PubMed, ScienceDirect, Web of Science, Google Scholar, and Scopus databases, and 35 articles were selected in total. Results: By reviewing the studies, it was found that areca nut products cause periodontal disease as well as oral lesions, which can become malignant with continuing use. Conclusion: Areca nut product chewing has deleterious effects on oral and dental health. Tooth fracture, periodontal disease, leukoplakia, lichenoid lesions, oral submucous fibrosis (OSF), and oral cancer can be correlated with areca nut use. Therefore, public health proceeding to discontinue areca nut consumption is advised to control premalignant and malignant lesions, such as OSF and oral cancer.